(untitled) (Journal of Engineering, 2003)
This Investigation was conducted activated carbon study the removal of dyes from waste water in the textile cotton industry Three different industrial dyes were used, these are direct blue, sulphure black and vat yellow with the following maximum concentrations in solution The method used is adsorption on of 6,10 and 16 ppm respectively The results showed that adsorption onto activated carbon with surface area of 626 m³/g to be very effective for the removal of the different dyes considered, where the percent removal was 96.75% 987 7% and 98.4% for direct blue, sulphure black and vat and vat yellow respectively